2011
DOI: 10.1016/j.rmed.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

CPAP increases exercise tolerance in obese subjects with obstructive sleep apnea

Abstract: Obese subjects commonly suffer from exertional dyspnea and exercise intolerance. Preliminary evidence suggests that treatment with nocturnal continuous positive airway pressure (nCPAP) may improve dyspnea in obese patients with obstructive sleep apnea (OSA), but the effect on exercise tolerance is unknown. This study sought to investigate whether nCPAP improves exercise tolerance and exertional dyspnea in obese patients with OSA. Obese patients prescribed nCPAP for moderate/severe OSA and without cardiopulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…However, few studies have documented increases in VO 2peak [48,49] and HRR [49] following CPAP treatment similar to the present study's findings, and others have failed to note VO 2peak improvements with CPAP use [38,50]. As the effects of CPAP on SNS hyperactivity are dependent upon compliance [51] and lost with CPAP withdrawal [52], exercise training may be a beneficial adjunct therapy to promote cardiovascular health in adults with OSA.…”
Section: Discussionsupporting
confidence: 77%
“…However, few studies have documented increases in VO 2peak [48,49] and HRR [49] following CPAP treatment similar to the present study's findings, and others have failed to note VO 2peak improvements with CPAP use [38,50]. As the effects of CPAP on SNS hyperactivity are dependent upon compliance [51] and lost with CPAP withdrawal [52], exercise training may be a beneficial adjunct therapy to promote cardiovascular health in adults with OSA.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have examined this question but provide conflicting results. Although an improvement in maximal exercise performance has been observed after varying treatment durations from 1 week to 8 months [48][49][50][51], other studies have not reported enhanced V′O 2 peak after 1-3 months of continuous positive airway pressure (CPAP) treatment [10,52,53]. These inconsistencies may be due to differences in treatment adherence, disease severity or physical activity levels.…”
Section: Potential Physiological Mechanismsmentioning
confidence: 99%
“…Indeed, it may be bidirectional. CPAP therapy increased exercise tolerance in obese individuals with OSA, 38 suggesting that OSA may exert a physiological influence that blunts capacity to engage in vigorous exercise activity. Conversely, longitudinal data suggest that exercise independently decreases the incidence of moderate-severe OSA.…”
mentioning
confidence: 99%